Cultivating Food Safety Together: Insights About the Future of Produce Safety in the U.S. Controlled Environment Agriculture Sector - Allyson N. Hamilton; Kristen E. Gibson; Mary Anne Amalaradjou; Christopher W. Callahan; Patricia D. Millner; Sanja Ilic; Melanie L. Lewis Ivey; Angela M. Shaw (Journal of Food Protection, 2023)
Controlled environment agriculture (CEA) is a rapidly growing sector that presents unique challenges and opportunities in ensuring food safety. This manuscript highlights critical gaps and needs to promote food safety in CEA systems as identified by stakeholders (n=47) at the Strategizing to Advance Future Extension and Research (S.A.F.E.R.) CEA conference held in April 2023 at The Ohio State University’s Ohio CEA Research Center. Feedback collected at the conference was analyzed using an emergent thematic analysis approach to determine key areas of focus. Research-based guidance is specific to the type of commodity, production system type, and size. Themes include the need for improved supply chain control, cleaning, and sanitization practices, pathogen preventive controls and mitigation methods and training and education. Discussions surrounding supply chain control underscored the significance of the need for approaches to mitigate foodborne pathogen contamination. Effective cleaning and sanitization practices are vital to maintaining a safe production environment, with considerations such as establishing standard operating procedures, accounting for hygienic equipment design, and managing the microbial communities within the system. Data analysis further highlights the need for risk assessments, validated pathogen detection methods, and evidence-based guidance in microbial reduction. In addition, training and education were identified as crucial in promoting a culture of food safety within CEA. The development of partnerships between industry, regulatory, and research institutions are needed to advance data-driven guidance and practices across the diverse range of CEA operations and deemed essential for addressing challenges and advancing food safety practices in CEA. Considering these factors, the CEA industry can enhance food safety practices, foster consumer trust, and support its long-term sustainability.